Bumdes Marketing Strategy and the Role of Village Government in Bumdes Development: A Case Study on Bumdes Terus Jaya Sehati - Mulya Rizki Anugrah, Ce; Suciati, Fithri; Safitri, Niken (KnE Social Sciences, 2022)
Village-owned enterprises or Bumdes are a source of village strength to support and improve the village economy by empowering village communities, village development, and assisting underprivileged residents in contributing toward the advancement of their village. Many Bumdes are scattered across Indonesia, one of which is Bumdes Terus Jaya Sehati, located in the Sukajaya Village, Sukabumi Regency. This Bumdes has succeeded in managing and developing village businesses within its territory. The role of the village government is certainly one of the important factors in the success of a village-owned business unit. To find out, researchers used descriptive research methods with a qualitative approach to study the ongoing activities and processes in Bundes. Research was conducted through interviews, observation, and documentation. The results of the study show that the marketing strategy carried out by the Bumdes Terus Jaya Sehati using the mixing method has been effective, and the role of the Sukajaya Village Government in developing the Bumdes Terus Jaya Sehati has been very good starting from the assistance to the evaluation stage. Keywords: Bumdes, marketing strategy, village government, village development